Efficacy and safety of antibiotic agents in the treatment of rosacea: a systemic network meta-analysis - Xiao, Wenqin; Chen, Mengting; Wang, Ben; Huang, Yingxue; Zhao, Zhixiang; Deng, Zhili; Xie, Hongfu; Li, Ji; Tang, Yan (Frontiers in Pharmacology, 2023)
Background: Antibiotics are considered the backbone of rosacea management, especially for controlling inflammatory papules and pustules. We aim to evaluate the efficacy and safety of varied prescriptions and doses of antibiotics in treating rosacea by network meta-analysis. Methods: In this study, we compared all available randomized controlled trials (RCTs) that have studied systemic and topical antibiotics and placebo in rosacea therapy. We searched databases such as the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, PubMed, Web of Science, and LILACS for published and unpublished RCTs on ClinicalTrials.gov before April 2023. The primary outcome was the improvement of the Investigator's Global Assessment (IGA) scores, and the secondary outcomes consisted of the improvement of the Patient's Global Assessment (PaGA) scores, Clinician's Erythema Assessment (CEA) scores, and adverse events (AEs). We used Bayesian random effects models for multiple treatment comparisons. Results: We identified 1,703 results through these databases. Thirty-one randomized trials with 8,226 patients were included. The heterogeneity and inconsistency between the trials were low, with a low risk of bias of all trials. Oral doxycycline 40 mg, minocycline 100 mg, and minocycline 40 mg, as well as topical ivermectin and metronidazole 0.75%, were effective in treating papules and pustules, thereby decreasing IGA in rosacea. Among these, minocycline 100 mg ranked top in efficacy. As for improving the PaGA scores, topical ivermectin, metronidazole 1%, and systemic oxytetracycline were effective, of which oxytetracycline worked the best. Both doxycycline 40 mg and metronidazole 0.75% presented no therapeutic effect for erythema. Considering the safety of the agents, systemic application of azithromycin and doxycycline 100 mg significantly increase the risk of AEs. Conclusion: Our review suggests that a high dosage of systemic minocycline is the most effective in treating rosacea phenotypes with papules and pustules with a low risk of AEs. However, there were no sufficient evidence-based data in exploring the influence of antibiotics on erythema. The phenotype of rosacea should be taken into consideration along with benefit and safety when making prescriptions due to AEs. Clinical Trial Registration: NCT(2016): http://cochranelibrary-wiley.com/o/cochrane/clcentral/articles/962/CN-01506962/frame.html NCT(2017): http://cochranelibrary-wiley.com/o/cochrane/clcentral/articles/764/CN-01565764/frame.html